INFLUENCE OF BEAM HEIGHT-COLUMN WIDTH RATIO ON SEISMIC BEHAVIOR OF RC MOMENT RESISTING FRAMES - A. Khalili; F. Nateghi Alahi (مهندسی عمران شریف)
Most reputable international design codes have included provisions for achieving ductile behavior and avoiding brittle and hazardous behavior in reinforced concrete frames. These provisions aim to achieve the concept of the weak beam-strong column, where plastic hinges during an earthquake occur first in the beams. Analysis of frequent and repetitive failures in strong earthquakes in recent decades of reinforced concrete structures shows that the strong beam-weak column failure mode typically leads to severe damage in these structures. The frequent occurrence of this failure mode can be attributed to two main factors. Firstly, stiffer beams are often used against more flexible columns due to the absence of seismic provisions that limit the relation between beam height and column width, which results in column severe damage to the columns and, finally, collapse of them. Secondly, the effect of the cast-in-situ slab in increasing the negative flexural strength of the beam is often underestimated or ignored, leading to the flexural strength of the columns being less than that of the beams. A series of computational models were created and analyzed in a parametric study to assess the impact of the ratio of beam height to column width on the seismic performance of MRFs. Before that, the FEA performance was validated by comparing its results with experimental data. The findings emphasize the urgent need for a new seismic provision that limits the beam height to column width ratio to a maximum of 1.25. Also, it is indicated that the values of effective slab width obtained from the provisions of ACI and EC8 are insufficient to ensure the implementation of the weak beam-strong column design methodology. Findings demonstrate that the value of effective slab width is minimally impacted by the beam height when the ratio of longitudinal beam height to column width ( h_lb⁄C ) is less than 1.5.